Ovarian cancer: early detection, angiogenesis, lymphangiogenesis and current prospects for therapy - Wiertel, Iwona; Bednarek, Wiesława; Czekierdowski, Artur; Kotarski, Jan (Polish Journal of Public Health, 2015)
I Chair and Department of Gynecological Oncology and Gynecology is a specialist research center providing help in diagnostics and treatment of gynecological malignancies. The research work is focused on the processes of angiogenesis and lymphangiogenesis. Development of blood and lymphatic vessels is subject to research in a wide range of malignancies, including ovarian cancer, endometrial cancer and uterine sarcomas. Angiogenesis in malignancies of the female genital tract is investigated by using some modern 3D sonography that uses high-definition blood flow imaging. Ovarian Tumors and Early Ovarian Cancer Detection unit was established in 2002 and since that time more than 3500 patients with difficult to diagnose tumors have been consulted and treated in the Department. Ovarian cancer immunology studies are the second leading research fiekld in the 1st Chair Department of Gynecological Oncology and Gynecology. The Department is well equipped with diagnostic devices as well as a scientific laboratory. This allows for studies in the fields of imaging of masses, their immunology, biochemistry and molecular biology. Understanding immunological response in patients with ovarian cancer is the key to develop new, effective therapies, including immunological vaccines. In this area we are cooperating with prominent international research centers: Department of Surgery, University of Michigan and Department of Microbiology and Immunology, University of Arkansas. Results of our research are published in both Polish and international journals specializing in fields of gynecology, oncology, immunology and basic science.